ANALISA PEMIKIRAN EKONOMI IBNU TAIMIYAH TENTANG WILAYATUL HISBAH DALAM BADAN METROLOGI DEPARTEMEN PERDAGANGAN REPUBLIK INDONESIA - Aziz Abdurrahman (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2023)
Islam is a universal religion. He not only regulates the procedure for worshiping Allah, but also regulates how to live the lives of other human beings, both to fellow Muslims and non-Muslims. Among the things that get great attention by Islam is economic affairs. And Muslim scholars take an important role in this. Among Islamic figures who have not escaped attention is Syaikhul Islam Ibn Taimiyah. The figure who is called a reformer has produced phenomenal works of his time. Among his works which discuss certain aspects of Islamic Economics is the book Al-Hisbah Fil Islam or Qaa'idah fil Hisbah. As a country with the largest Muslim population in the world, Indonesia will never be separated from life's problems, including the economy. Economic activities carried out by the community, such as buying and selling, certainly require control from the government so that these activities run well. Among the government agencies that specifically handle buying and selling activities in the community is the metrology center. Because in the facts that were found there were several frauds committed by some unscrupulous traders. Researchers used library research (library research). In researching about wilayatul hisbah, researchers make the book Al-Hisbah as the primary source in Ibn Taimiyah's thoughts, besides that researchers also use scientific journals as references in research. For the Al-Hisbah book, the researcher used the oldest printing in the world today, namely the Matba'ah al-Mu'ayyadah Cairo Egyptian 1990 M. The approach in the research carried out was heuristic, biographical and interpretive research. The results in this study indicate that the Ministry of Trade's Metrology Center has in general carried out the Hisbah function according to Ibnu Taimiyah. The Metrology Center has the task of supervising trade as an effort to prevent acts of fraud and fraud. The task carried out by the Metrology Center is to carry out inspections of measuring, measuring, weighing and equipment (UTTP) in order to assess and match the type of UTTP tool that is appropriate or not, namely with regulations. The difference between the Hisbah and the Metrology Center is that the Hisbah has the authority to prevent possible fraud by improving morals or morals, because the main purpose of the Hisbah is amar ma'ruf nahi munkar, while the Metrology Center's role is only in the aspect of truth and legitimacy of the UTTP tool used by traders.